纯电动汽车用自动变速器传动参数优化与仿真 - 陈奇; 冯永恺; 杨昊仁; 任树桢 (Jixie chuandong)
Aiming at the problem of low efficiency of drive motor and short driving range of the electric vehicle,according to the requirements of the vehicle dynamic performance and treat the efficiency of drive motor as optimal target,the drive motor is matched and the automatic transmission transmission parameters are optimized and simulated.The results show that the method not only met the acceleration,gradeability and maximum speed of the electric vehicle,but also improved the efficiency of the motor.